Electric field-controlled crossover effect in oxygen-deficient titanium-oxide memory bits. (December 2019) - Alagoz, H.S.; Davies, M.; Zhong, Y.; Chow, K.H.; Jung, J.
Abstract: In this letter, we report an unusual crossover in the current-voltage characteristics of forming-free titanium oxide-based memory bits. The voltage at which crossover between high and low resistance states take place, V cr gradually shifts to lower bias values with either decreasing sweeping rates, increasing maximum scan voltage or increasing current compliance. Interestingly, the crossover effect is not pronounced for reduced-oxide based memory bits. The mechanism behind these changes in the I-V curves is discussed. Highlights: We report an unusual crossover effect in the current-voltage characteristics of forming free titanium-oxide based memory bits. The crossover effect is observed only when the bilayer is engineered with different O/Ti ratio within the titanium oxide switching layer. Crossover voltage shifts to lower values with decreasing sweep rates, increasing maximum voltage scan or current compliance.